THROMBECTOMY OF A BASILAR ARTERY - Karce, Ateme; Janevski, Petar; Aliji, Vjollca; Daskalov, Dejan; Arifi, Njomza (Journal of Morphological Sciences, 2025)
Mechanical thrombectomy is a type of minimally invasive procedure in which an interventional radiologist uses specialized equipment to remove a clot from a patient’s artery. Using fluoroscopy, or continuous x-ray, the doctor guides instruments through patient’s arteries to the clot, extracting the clot all at once. The radiologist starts the procedure by making a small incision in either the wrist or the abdomen, giving them an access to an artery. After making the incision, the doctor threads a catheter through the artery to the clot. Next, a tiny net-like device called a stent retriever is inserted into the catheter and guided to the blockage. Then, the stent retriever is pushed through the clot. After the stent retriever is through, it expands to the size of the artery wall. At this point, the stent retriever has captured the clot, and the doctor is able to pull it out backwards, removing the clot entirely. Keywords:  thrombectomy ,  stroke  stent, interventional radiology.